Pengaruh Literasi Keuangan, Digital Marketing dan Inovasi Produk Terhadap Kinerja Keuangan pada UMKM Kuliner di Kecamatan Serengan Surakarta - Shidiq, Yusril; Wibowo, Edy; Setyaningsih (Teewan Journal Solutions, 2025)
In a competitive business landscape, adequate financial literacy is a basic asset for every business person. By understanding financial principles, businesses can allocate resources effectively and efficiently. In addition, the utilisation of digital marketing and continuous product innovation are also keys to success in facing dynamic market challenges. These three elements are interrelated and support each other in achieving business goals. This study examines in depth the characteristics and performance of culinary Micro, Small and Medium Enterprises (MSMEs) operating in the Serengan District area, Surakarta City. Through a survey approach, this study aims to identify factors that affect financial performance in culinary MSMEs in that location. The research sample of 81 respondents was obtained using purposive sampling technique from a total population of 328 culinary MSMEs. Multiple linear regression analysis is used to test the effect of independent variables on the dependent variable, and is complemented by the t test, F test, and coefficient of determination to confirm the significance of the model. The results of the research and discussion can be concluded that: 1) Financial literacy has no significant effect on the financial performance of culinary MSMEs in Serengan District, Surakarta. 2) Digital marketing has a significant effect on the financial performance of culinary MSMEs in Serengan District Surakarta. 3) Product innovation has a significant